INFLUENCE OF SPINDLE SPEED ON ALUMINUM SURFACE ALLIANCE IN CONVENTIONAL AND CNC LATHE MACHINE - X. Chen; C. Lin; I.S. Cebro (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2018)
The level of surface roughness of a metal in the lathe process depends on the process; spindle rotation, cutting speed, feed speed, cutting tool material, cooling process and machine condition. The objective of this research is to know spindle rotation relationship to aluminum surface roughness on the conventional lathe and CNC lathe. The test specimens amounted to 36 for the conventional lathe and 36 for the CNC lathe. Spindle rotation varied at 9 levels of rotation ie 90 rpm, 100 rpm, 155 rpm, 190 rpm, 260 rpm, 320 rpm, 440 rpm, 540 rpm and, 740 rpm. Each spindle level rotates four specimens. The measurement results show that on the conventional lathe the higher the spindle spin the higher the level of surface roughness, while on the CNC lathe the higher the spindle spin the lower the surface roughness level.